2008
DOI: 10.1038/nrg2452
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis — the essential role of gene interactions in the structure and evolution of genetic systems

Abstract: Epistasis, or interactions between genes, has long been recognized to be fundamentally important to understanding both the structure and function of genetic pathways and the evolutionary dynamics of complex genetic systems. With the advent of high throughput functional genomics and the emergence of systems approaches to biology, as well as a newfound ability to pursue the genetic basis of evolution down to specific molecular changes, there is a renewed appreciation both for the importance of studying gene inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
1,254
0
18

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,364 publications
(1,282 citation statements)
references
References 109 publications
10
1,254
0
18
Order By: Relevance
“…Other recent studies have found large-scale epistasis in HIV-1 virus genes [5,6], and in mitochondrial transfer RNA from eukaryotes [7]. These three examples constitute only a very small snapshot of a much larger body of literature, which suggests that epistasis is widespread throughout the living world [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent studies have found large-scale epistasis in HIV-1 virus genes [5,6], and in mitochondrial transfer RNA from eukaryotes [7]. These three examples constitute only a very small snapshot of a much larger body of literature, which suggests that epistasis is widespread throughout the living world [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of evolution, it is helpful to quantify epistasis in terms of the fitness that selection can act on 1 [9]. Epistasis manifests in many different ways.…”
Section: Introductionmentioning
confidence: 99%
“…interactions, where the effect of one locus depends on the genotype of another locus (Phillips 2008) may also play a role, especially given that we have earlier detected epistatic interactions between tameness QTL (Albert et al 2009). The large number of genes and pathways described in the literature influencing behavioral traits related to tameness such as anxiety and aggression makes it plausible that genes in multiple biological pathways could have reacted to the strong selection in these rats (Hovatta and Barlow 2008;Le-Niculescu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic architecture involves not only the number of genes and the distribution of fitness effects, but also the interactions between alleles at various loci (epistasis), the degree to which variation in a particular gene affects multiple traits (pleiotropy), and the form (if any) of interactions between a genotype and environment. For example, epistasis may affect the chances that beneficial alleles will spread [4,5] and pleiotropy may constrain adaptive evolution [6]. A related and as yet unresolved controversy has long surrounded the relative importance of proteincoding versus cis-regulatory adaptive changes.…”
Section: Introductionmentioning
confidence: 99%